Insulin-like growth factor binding protein 5b of Trachinotus ovatus and its heparin-binding motif play a critical role in host antibacterial immune responses via NF-κB pathway - Du, Hehe; Zhou, Yongcan; Du, Xiangyu; Zhang, Panpan; Cao, Zhenjie; Sun, Yun (Frontiers in Immunology, 2023)
Insulin-like growth factor binding protein 5 (IGFBP5) exerts an essential biological role in many processes, including apoptosis, cellular differentiation, growth, and immune responses. However, compared to mammalians, our knowledge of IGFBP5 in teleosts remains limited. In this study, TroIGFBP5b, an IGFBP5 homologoue from golden pompano (Trachinotus ovatus) was identified. TroIGFBP5b contains a signal peptide (SP) and a heparin-binding motif (HBM) in the nuclear localization signal (NLS) domain. The TroIGFBP5b mRNA expression level was higher in some immune-related tissues, such as the liver, spleen, and head kidney, and upregulated after bacterial stimulation. In vivo, TroIGFBP5b overexpression significantly improved the antibacterial immunity of fish. In contrast, TroIGFBP5b knockdown significantly decreased this ability. To better understand the mechanism of its role in antibacterial immunity, we constructed a mutant in which HBM was deleted, named TroIGFBP5b-ΔHBM. Subcellular localization was confirmed by observing golden pompano snout (GPS) cells transfected with GFP-recombinant plasmid and immunoblotting nuclear and cytoplasmic cellular extracts, and the results showed that TroIGFBP5b and TroIGFBP5b-ΔHBM were both present in the cytoplasm of GPS cells. After stimulation, TroIGFBP5b-ΔHBM lost the ability to transfer from the cytoplasm to the nucleus. In addition, purified recombinant TroIGFBP5b (rTroIGFBP5b) promoted the proliferation of head kidney lymphocytes (HKLs) and phagocytosis of head kidney macrophages (HKMs), whereas rTroIGFBP5b-ΔHBM, suppressed these facilitation effects. Moreover, the in vivo antibacterial ability of TroIGFBP5b was suppressed, and the effects of promoting expression of proinflammatory cytokines in immune tissues were nearly lost after HBM deletion. Furthermore, TroIGFBP5b induced nuclear factor-κB (NF-κB) promoter activity and promoted nuclear translocation of p65, while these effects were inhibited when the HBM was deleted. Taken together, our results suggest that TroIGFBP5b plays an important role in golden pompano antibacterial immunity and activation of the NF-κB signalling pathway, providing the first evidence that the HBM of TroIGFBP5b plays a critical role in these processes in teleosts.